Musical instrumental reading affects middle cerebral blood flow and cognitive function - Kawasaki, Ai; Hayashi, Naoyuki (Frontiers in Physiology, 2022)
Playing a musical instrument includes reading music scores, playing, and listening in parallel. It is unclear which of these activities are responsible for an increase in cerebral blood flow. We investigated the factors increasing middle cerebral artery velocity (MCAv) during musical performance, and examined whether playing and reading music affects cognitive function. Seventeen musicians played an instrument with reading music, played music from memory, and read music scores in a randomized order, for 10 min each. The MCAv was continuously recorded from 5 min before to 10 min after the performance. A Stroop test was performed before and after performance. The MCAv increased significantly with reading music, playing from memory, and reading music. Stroop test scores increased significantly after music reading. These findings suggest that both music reading and playing an instrument are involved in the increase in MCAv during music performance. Cognitive function was transiently improved by playing musical instruments.